2017
DOI: 10.1111/padm.12333
|View full text |Cite
|
Sign up to set email alerts
|

‘We are this hybrid’: Members’ search for organizational identity in an institutionalized public–private partnership

Abstract: There has been significant scholarly interest in organizational hybridity, the combination of multiple institutional logics in one entity. However, the extant research has mainly studied the implications for organizations and individuals, neglecting the challenges for organizational members as a collective. To mitigate, this article examines how members of a British institutionalized public–private partnership grapple with the question of what their organization may be, highlighting the confusion they are expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 75 publications
(151 reference statements)
0
14
0
1
Order By: Relevance
“…Using the Sociology of Professions to Compare Public Values in Public Administration and Urban Planning Literatures"). There is also organizational identity which refers to how members construct and enact their organization (Reissner 2019). Whether at the individual, professional/occupational, or organizational levels, public servant identities are not fixed.…”
Section: Bricolagementioning
confidence: 99%
See 1 more Smart Citation
“…Using the Sociology of Professions to Compare Public Values in Public Administration and Urban Planning Literatures"). There is also organizational identity which refers to how members construct and enact their organization (Reissner 2019). Whether at the individual, professional/occupational, or organizational levels, public servant identities are not fixed.…”
Section: Bricolagementioning
confidence: 99%
“…Hybridity is generally understood on three scales. The first refers to hybridity on a micro-level and relates to how individuals understand themselves and their identities within organizations (Reissner 2019), as we discussed in the previous section. The second focuses on different types of organizational features, such as government services provided by private or nongovernment bodies (Ugyel 2014).…”
Section: Hybriditymentioning
confidence: 99%
“…This inquiry aims to fill several gaps in the literature. Researchers have called in for further research into identity claim and understanding to comprehend the construction of the identity and if one influences the other (Ran & Duimering, ; Ran & Golden, ; Ravasi & Schultz, ; Reissner, ). Further research is suggested to understand how nonprofits construct their identity (Feldner & Fyke, ; Hansen & Milburn, ; Young, ).…”
Section: Organizational Identity and The Non‐profit Sectormentioning
confidence: 99%
“…(Bourgault and van Dorpe 2013;van Bockel and Noordegraaf 2006). Finally, at a collective level, the term organizational identity refers to "what members perceive, feel and think about their organizations" (Hatch and Schultz 1997, p. 357) (Rondeaux 2006;Skålén 2004) and can be understood as the outcome of collective sensemaking which, once constructed by members, influences how they "enact" their organization and its environment (see Reissner 2019).…”
Section: Background: Identity and Public Sector Changementioning
confidence: 99%
“…It also contributes to greater institutional complexity prompting more identity work on the part of its members but also making the construction of a coherent organizational identity more challenging. For example, in Reissner's (2019) investigation of the identity of a public-private partnership she detected diverging accounts of the meaning of the partnership, regardless of the position or status of the individual: some were enthusiastic, others skeptical, and still others unsure of what it was or what it meant. Such divergence and incoherence and confusion about organizational identity, she argues, constitute a challenge for creating and sustaining hybrid organizational arrangements.…”
Section: Organizational Identitymentioning
confidence: 99%